Highly Concentrated, Ultrathin Nickel Hydroxide Nanosheet Ink for Wearable Energy Storage Devices. Issue 40 (1st September 2017) - Shi, Peipei; Chen, Rong; Hua, Li; Li, Li; Chen, Ruyi; Gong, Yujiao; Yu, Chenyang; Zhou, Jinyuan; Liu, Bin; Sun, Gengzhi; Huang, Wei
Abstract: Solution‐based techniques are considered as a promising strategy for scalable fabrication of flexible electronics owing to their low‐cost and high processing speed. The key to the success of these techniques is dominated by the ink formulation of active nanomaterials. This work successfully prepares a highly concentrated two dimensional (2D) crystal ink comprised of ultrathin nickel hydroxide (Ni(OH)2 ) nanosheets with an average lateral size of 34 nm. The maximum concentration of Ni(OH)2 nanosheets in water without adding any additives reaches as high as 50 mg mL −1, which can be printed on arbitrary substrates to form Ni(OH)2 thin films. As a proof‐of‐concept application, Ni(OH)2 nanosheet ink is coated on commercialized carbon fiber yarns to fabricate wearable energy storage devices. The thus‐fabricated hybrid supercapacitors exhibit excellent flexibility with a capacitance retention of 96% after 5000 bending–unbending cycles, and good weavability with a high volumetric capacitance of 36.3 F cm −3 at a current density of 0.4 A cm −3, and an energy density of 11.3 mWh cm −3 at a power density of 0.3 W cm −3 . As a demonstration of practical application, a red light emitting diode can be lighted up by three hybrid devices connected in series. Abstract : A highly concentrated 2D crystal ink comprised of ultrathin Ni(OH)2 nanosheets with an average lateral size of 34 nm is prepared. The Ni(OH)2 nanosheet ink can be printed on commercialized carbon fiber yarn for wearable energy storage devices. The thus‐fabricated hybrid supercapacitors exhibit good flexibility and weavability with much improved capacitance and energy density.